Commensal Enterobacteriaceae as reservoirs of extended-spectrum beta-lactamases, integrons, and sul genes in Portugal - Machado, Elisabete; COQUE, TERESA M.; Cantón, Rafael; Sousa, João C.; Peixe, Luísa (Frontiers in Microbiology, 2013)
Bacteria colonizing the human intestine have a relevant role in the spread of antimicrobial resistance. We investigated the faecal carriage of extended-spectrum beta-lactamase (ESBL)-producing Enterobacteriaceae in healthy humans from Portugal and analysed the distribution of sul genes and class 1 and 2 integrons. Faecal samples (n=113) were recovered from healthy persons (North/Centre of Portugal, 2001-04) and plated on MacConkey agar with and without ceftazidime (1mg/L) or cefotaxime (1mg/L). Isolates representing different morphotypes/plate and antibiotic susceptibility patterns (n=201) were selected. Isolates resistant to sulfonamides and/or streptomycin, gentamicin and trimethoprim were screened (PCR, sequencing) for sul genes (sul1, sul2, sul3) and class 1 and 2 integrons. Presence of ESBLs was inferred using the DDST and further confirmed by PCR and sequencing. ESBL producers were selected for clonal analysis, plasmid characterization and conjugation assays by standard methods. ESBL-producing isolates were found in 1.8% (2/113) of samples, corresponding to Escherichia coli of phylogroups A (n=1) and B1 (n=1) carrying transferable blaCTX-M-14 and the new blaTEM-153, respectively. A 80kb IncK-blaCTX-M-14 was found, being highly related to that widely spread among CTX-M-14 producers of humans and animals from Portugal and other European countries. sul genes were found in 88% (22/25;sul2-60%, sul1-48%, sul3-4%) of the sulfonamide resistant isolates. Class 1 integrons were more frequently found than class 2 (7% vs 3%). Interestingly, gene cassette arrangements within these platforms were identical to those commonly observed among Enterobacteriaceae from Portuguese food-producing animals, although aadA13 is here firstly described in Morganella morganii. These results reinforce the relevance of human commensal flora as reservoir of clinically relevant antibiotic resistance genes including blaESBLs, and highly transferable genetic platforms as IncK epidemic plasmids.